Heavenly Returns: What the Abrahamic Faiths Teach Us About Financial and Spiritual Well-being - Shafinah Begum, Abdul Rahim (IAIS Malaysia, 2022)
Heavenly Returns is an extraordinary product from the collaborative work of two co-authors of different faith sharing a similar understanding of the Abrahamic traditions in aligning our financial and spiritual lives. Together, Gary Moore a retired Christian financial manager and Yaqub Mirza, a Muslim investment manager attempt to demonstrate the similarities between the relevant contents of the Bible and the Quran despite the theological and cultural differences in Christianity and Islam.